Vasoactive Management of Pulmonary Hypertension and Ventricular Dysfunction in Neonates Following Complicated Monochorionic Twin Pregnancies: A Single-Center Experience - Lukas Schroeder; Leon Soltesz; Judith Leyens; Brigitte Strizek; Christoph Berg; Andreas Mueller; Florian Kipfmueller (MDPI AG, 2024)
Objectives: Twins resulting from a complicated monochorionic (MC) twin pregnancy are at risk for postnatal evolution of pulmonary hypertension (PH) and cardiac dysfunction (CD). Both pathologies are important contributors to short- and long-term morbidity in these infants. The aim of the present retrospective single-center cohort study was to evaluate the need for vasoactive treatment for PH and CD in these neonates. Methodology: In-born neonates following a complicated MC twin pregnancy admitted to the department of neonatology of the University Children's Hospital Bonn (UKB) between October 2019 and December 2023 were screened for study inclusion. Finally, 70 neonates were included in the final analysis, with 37 neonates subclassified as recipient twins (group A) and 33 neonates as donor twins (group B). Results: The overall PH incidence at day of life (DOL) 1 was 17% and decreased to 6% at DOL 7 (p = 0.013), with no PH findings at DOL 28. The overall incidence of CD was 56% at DOL 1 and decreased strongly until DOL 7 (10%, p = 0.015), with no diagnosis of CD at DOL 28. The use of dobutamine, norepinephrine, and vasopressin at DOL 1 until DOL 7 did not differ between the subgroups, whereas the dosing of milrinone was significantly higher in Group B at DOL 1 (p = 0.043). Inhaled nitric oxide (iNO) was used in 16% of the cohort, and a levosimendan therapy was administered in 34% of the neonates. One-third of the cohort was treated with oral beta blockers, and in 10%, an intravenous beta blockade (landiolol) was administered. The maximum levosimendan vasoactive-inotropic score (LVISmax) increased from DOL 1 (12.4 [3/27]) to DOL 2 (14.6 [1/68], p = 0.777), with a significant decrease thereafter as measured at DOL 7 (9.5 [2/30], p = 0.011). Conclusion: Early PH and CD are frequent diagnoses in neonates following a complicated MC twin pregnancy, and an individualized vasoactive treatment strategy is required in the management of these infants.